Enchondroma Protuberans of the Ulna in a Pediatric Patient: A Case Report. Issue 3 (July 2016) - Lasater, Peter; Steensma, Matthew Richard; Patthanacharoenphon, Cameron; Davis, Mary M.
Abstract : Case: We report the case of a 3-year-old boy who presented with a distal ulnar fracture through a mixed sclerotic and lytic expansile lesion. The underlying lesion, an enchondroma protuberans, can mimic either benign or malignant bone tumors. It was successfully treated with casting and intralesional treatment. Conclusion: Enchondroma protuberans is a rare entity that mimics enchondroma, osteochondroma, periosteal chondroma, or chondrosarcoma. Diagnosis is typically made through both radiographic and histologic means. In this case, the pathologic fracture was successfully treated with casting followed by intralesional curettage and bone-grafting. There was no evidence of recurrence at 18 months.